MADRASAH HEAD'S STRATEGY IN INCREASING THE NUMBER OF STUDENTS AT MTs PLUS ACCORDING TO TAQWA BAWEAN - Nur Alfiyatus Sa’adah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
MTs Plus Nurut Taqwa has carried out student recruitment activities consistently, from year to year the number of students has increased, but in the 2023-2024 academic year, the number of students has decreased. This is related to the madrasa head's strategy for increasing the number of students. This type of research uses descriptive qualitative research methods. Data collection used direct observation in the field and interviews. The research data analysis technique uses Miles and Huberman analysis which consists of three stages of data acquisition analysis, namely data reduction, data exposure, and drawing conclusions or verification. The results of the research show that: first, the madrasa head's strategy in increasing the number of students at MTs Plus Nurut Taqwa includes various strategies, namely using outreach to elementary/MI schools, placing advertisements via social media and making brochures, a strategy from home to home, in collaboration with MTs Plus Nurut Taqwa graduates and collaboration with community leaders. Second, supporting factors and inhibiting factors for the madrasa head's strategy in recruiting new students at Mts Plus Nurut Taqwa. Supporting factors include the image of the kyai and chairman of the Foundation being widely known by the local community, the public's trust in the Islamic boarding school under the care of the kyai and the nyai, the MTs Plus Nurut Taqwa Institution which is located in the Islamic boarding school environment and students must board if they want to study at MTs Plus Obedience to Taqwa. Implementation of teaching and learning at MTs Plus Nurut Taqwa which is related to Islamic boarding schools. There is encouragement from student parents in student recruitment activities. The inhibiting factors are the student admissions committee, costs, inadequate infrastructure, human resources, and the number of Tsanawiyah madrasas at the same level.